IMPLEMENTASI KEBIJAKAN ZONASI PASAR TRADISIONAL DAN PASAR MODERN (STUDI DI KABUPATEN PURBALINGGA) - Kupita, Weda; Bintoro, Rahadi Wasi (Jurnal Dinamika Hukum, 2012)
Regency area that investment  increased  more  relatively  is  Purbalingga. One of the Increased  industrial sector is retail, whether traditional market and modern market formats such as alfamart and Indomart.  Today almost every district in Purbalingga have more than one retail market  in a modern format, such as in Kalimanah District, Padamara District, Bobotsari District and Bojongsari District. Therefore, researchers are interested to discuss about the implementation of zo-ning policies of traditional markets and modern markets in Purbalingga and what factors are likely to affect the implementation of zoning policies of tradisional market and a modern market in Purbalingga.Based on the results there are un synchronized legislation in zonation of traditi onal market and modern market. The factors that affect in policy of zoning traditional market and modern market are the law, law enforcement, facilities and infrastructure, community, and cultural factors. Keywords : policy, traditional market, modern market